Breves contribuições da crítica pós-moderna para a análise dos movimentos sociais - Carlos A. Gadea (Universidade do Vale do Rio dos Sinos (UNISINOS), 2005)
The present text intends to do a theoretical and analytical approach from the so-called postmodern critic to the theory of social movements. First, it is introduced the main principles of the postmodern critic as evidenced by social theory. The focus lays on the construction of an analytic framework, which would lead to the criticism established by its interface with the theory of social movements. At least, it is offered a contribution to the clarification of those methodological and analytical principles and a theoretical landmark based on concrete themes, as well a theory of social movements, which cannot neglect the meaning nor the sense of postmodern critic in present days.